Persuasive review on clustering routing protocol-based algorithm in Wireless Sensor Networks - Panimalar.K, Kanmani.S (International Journal of Advanced Science and Technology, 2020)
In WSN, the sensor nodes built on an inadequate storage capability, transmission range, sensing range and energy sources. Due to limitation of critical resource like battery, finding an effective route for data transmission has the interest of current researchers. Routing is the foremost topic in Wireless Sensor Network that reveals the dissimilarities among wireless networks such as mobile and vehicular ad-hoc networks. Clustering is another topic that aggregates data and distributes evenly among the nodes, so that th+e elected Cluster Head (CH) can be alive for extended time. Routing protocols are liable for providing routes and entails high energy expenditure. This improve the outcome of designing energy efficient clustering routing algorithms to enhance the network lifespan, to provide scalability by utilizing low power in data transmission and other operation. In this paper, various efficient protocols have been deliberated and the goal is to provide a clear-cut coverage on the literature survey on these protocols till date.